2017
DOI: 10.1002/jmri.25809
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility weighted imaging and quantitative susceptibility mapping of the cerebral vasculature using ferumoxytol

Abstract: Purpose To demonstrate the potential of imaging cerebral arteries and veins with ferumoxytol using susceptibility weighted imaging (SWI) and quantitative susceptibility mapping (QSM). Materials and Methods The relationships between ferumoxytol concentration and the apparent susceptibility at 1.5T, 3T, and 7T were determined using phantom data; the ability of visualizing subvoxel vessels was evaluated using simulations; and the feasibility of using ferumoxytol to enhance the visibility of small vessels was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 38 publications
2
42
1
Order By: Relevance
“…However, QSM CBV estimates were similar to both R 2 *‐based approaches and no significant differences between CBV methods was found. It is likely that QSM underestimates susceptibility changes in venous blood after injecting ferumoxytol, as was observed in another study that injected a total dose of 4 mg FE/kg . In that study, researchers attributed the underestimation of venous blood susceptibility changes to problems with increased phase aliasing and effective vessel diameter.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…However, QSM CBV estimates were similar to both R 2 *‐based approaches and no significant differences between CBV methods was found. It is likely that QSM underestimates susceptibility changes in venous blood after injecting ferumoxytol, as was observed in another study that injected a total dose of 4 mg FE/kg . In that study, researchers attributed the underestimation of venous blood susceptibility changes to problems with increased phase aliasing and effective vessel diameter.…”
Section: Discussioncontrasting
confidence: 74%
“…It is likely that QSM underestimates susceptibility changes in venous blood after injecting ferumoxytol, as was observed in another study that injected a total dose of 4 mg FE/kg. 24 In that study, researchers attributed the underestimation of venous blood susceptibility changes to problems with increased phase aliasing and effective vessel diameter. In this study we used a multi-echo imaging approach, compared with the single-echo approach used in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QSM removes blooming artifacts and background field effects and can directly quantify USPIO uptake. It has previously been shown that tissue susceptibility increases linearly with the concentration of USPIOs . Therefore, using a previously established scaling factor of 59.6 ppm mL/mg at 1.5T, it can be estimated that the plaques scanned in this study contained a mean concentration of 22 ± 10 µg/mL.…”
Section: Discussionmentioning
confidence: 85%
“…It has previously been shown that tissue susceptibility increases linearly with the concentration of USPIOs . Therefore, using a previously established scaling factor of 59.6 ppm mL/mg at 1.5T, it can be estimated that the plaques scanned in this study contained a mean concentration of 22 ± 10 µg/mL. For quantitative analysis it would be necessary to acquire a precontrast scan to determine the baseline susceptibility value within the plaque and determine the increase created by the USPIO uptake.…”
Section: Discussionmentioning
confidence: 99%